A short qualitative exploration of the reporting and use of non-financial data in the context of the fitness check of the EU framework for public reporting by companies - Ingmar Jürgens; Katharina Erdmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
[Introduction] In the EU, large public-interest entities with more than 500 employees are required to disclose non-financial information, which is generally related to environmental, social and governance aspects, along with their traditional financial disclosure. Amending directive 2013734/EU (the so called "accounting directive"), Directive 2014/95/EU (commonly referred to as non-financial reporting directive, or NFRD). Public interest entities means listed companies, banks and insurance companies, as well as any additional categories of entity specified at the level of member States. This concerns approximately 6,000 companies and groups across the EU. The directive defines the reporting scope only in broad terms and in particular, in terms of mode and place of reporting, the directive leaves a lot of flexibility to the reporting entities. Against this background, the European Commission drafted non-binding guidelines in order to support companies in particular as regards their environmental and social disclosure. In addition, there have been further developments in the past few months. The European Commission launched a "Fitness check on the EU framework for public reporting by companies", which results were published in November 2019. As part of the Sustainable Finance Action Plan they furthermore updated the Non-Binding Guidelines on Non-Financial Reporting in June 2019, specifically with regard to the reporting of climate related information. In this context, DIW Berlin executed a mini-research project to contribute to the above mentioned fitness check; through a targeted literature review, exploring the consistency, quality and availability of ESG data across different types of entities and member states. This was complemented by a small survey, and a few longer interviews to get some additional qualitative information in relation to the use of and demand for ESG data by investment professionals. The focus lies on climate-related/ carbon data. Due to the qualitative character of the survey, one key contribution consisted in the identification of follow-up (research) questions, which are discussed in relation to each of the survey themes. The results are presented in this short report. We begin in Section 1 with the literature review, Section 2 contains the results of the conducted survey. Additional information can be found in the annex.
Keywords: 330